Vacuum-Sealing as a Treatment Option for Severe Anthracycline Extravasation in a Breast Cancer Patient - Rhiem, Kerstin (S. Karger GmbH, 2008)
BACKGROUND: Compared to peripheral venous access, central lines greatly reduce the incidence of cytotoxic extravasation. Although implantable vascular systems are widely used in oncology, extended extravasation lesions in cancer patients remain complicated. PATIENT AND METHOD: A 67-year-old female breast cancer patient suffered from an extended lesion of a catheter port extravasation. A vacuum-sealing therapy was initiated to accelerate the healing of the anthracycline-induced wound. RESULT: The vacuum-sealing technique allowed a fast and successful treatment of the extravasation lesion. CONCLUSION: Due to the myelosuppressive chemotherapy regimen, the risk of wound infections and prolonged healing processes is increased in cancer patients. Moreover, disruption or cancellation of anticancer therapies worsens the patients’ prognosis. To attenuate these complications the vacuum-sealing technique should be considered in wound management concepts.